Subjective Family Socioeconomic Status and Adolescents’ Attention: Blacks’ Diminished Returns - Shervin Assari; Shanika Boyce; Mohsen Bazargan (Children, 2020)
Background: Racial minorities, particularly non-Hispanic blacks (NHBs) in the US, experience weaker effects from their families’ socioeconomic status on tangible outcomes, a pattern called the Minorities’ Diminished Returns (MDRs) theory. These MDRs are frequently shown in the effects of the families’ socioeconomic status (SES) on NHB adolescents’ school performance. As a result of these MDRs, NHB adolescents from high SES families show a worse than expected school performance. The existing knowledge is, however, minimal about the role of attention in explaining the diminished returns of the families’ SES with regard to the adolescents’ outcomes. Aim: To investigate the racial differences in the effects of the subjective family SES on adolescents’ attention, we compared non-Hispanic white (NHW) and NHB adolescents to assess the effect of the subjective family SES on adolescents’ attention. Methods: This was a cross-sectional analysis that included 4188 adolescents from the Adolescent Brain Cognitive Development (ABCD) Study. The independent variable was the subjective family SES. The primary outcome was the adolescents’ attention to be measured by the stop-signal task (SST). The attention domain of the Child Behavior Checklist (CBCL) was also measured. Results: Overall, a high subjective family SES was associated with a higher task-based and CBCL-based attention. Race showed statistically significant interactions with subjective family SES in terms of adolescents’ attention outcomes. These interactions suggested that a high subjective family SES has smaller tangible effects on increasing the attention of NHB than NHW adolescents. Conclusion: The boosting effect of subjective family SES on attention is diminished for NHB rather than NHW adolescents. To minimize the racial gap in attention-related behaviors, such as school performance, we need to address the diminished returns of resources in the lives of NHB families. Not only should we equalize SES, but also increase the marginal returns of SES for racial minorities, particularly NHB families. Such efforts require public policies that empower NHB families to better leverage their SES resources and turn them into tangible outcomes. In addition, social policies should directly aim to alter the societal barriers that limit NHB families’ ability to effectively utilize their resources. Discrimination, segregation, and racism should be targets of our policy solutions.